ANALISIS STRATEGI PENETRASI PASAR DALAM MENINGKATKAN KEBERLANJUTAN BISNIS UMKM KULINER: STUDI KASUS PADA PRODUK MANGMIEE SHAN CULINARY - Thaliah Azka Ivani; Khafi Puddin; Fadli Agus Triansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The intensifying competition within Indonesia's culinary MSME sector necessitates that businesses, such as Mangmiee Shan Culinary, adopt precise growth strategies. This study aims to analyze the market penetration strategy employed by Mangmiee Shan Culinary to enhance business sustainability, while identifying the internal and external factors that influence its implementation. Using a qualitative approach with a single case study design, data were collected through in-depth interviews, field observations, and documentation, then analyzed using SWOT and Ansoff Matrix frameworks. The findings indicate that Mangmiee Shan Culinary focuses on a market penetration strategy through the optimization of digital platforms, competitive pricing, packaging innovation, and distribution expansion. The uniqueness of the product flavor and existing customer loyalty are identified as primary strengths, whereas limited production capacity and restricted distribution reach remain critical weaknesses that require resolution. This research contributes theoretically to the literature on culinary MSME strategies and offers practical guidance for similar enterprises in designing sustainable growth strategies.